Compared Cranial Osteology of Species of Leptoptilus (Lesson, 1831) (Aves, Ciconiidae) - Oliveira, Pamela Rayara de Souza; Donatelli, Reginaldo José; Neves, Arthur Serejo; Santos, Francisco das Chagas Vieira; Santos, Suely Silva; Nascimento, Muryllo do Santos; FERREIRA, GUILHERME JOSE BOLZANI DE CAMPOS; Guzzi, Anderson (Comunicata Scientiae, 2019)
The species of the Ciconiidae family (Ciconiiformes), commonly known as storks, exhibit a cosmopolite distribution, being represented by swamp birds of medium and large size. The present work aimed to describe minutely and comparatively the cranial osteology of Leptoptilus species. The study was performed based on the description of cranial bones of the species Leptoptilus dubius, L. crumeniferus, and L. javanicus. The studied specimens were previously prepared (dry crania and mandibles). Among the studied characteristics, it was possible to observe some structures of systematic importance, such as the zygomatic process, the temporal fossa, the ectethmoid, the superior maxilla, the quadrate bone that interconnects the palate, the neurocranium, and the mandible, performing a key role in the work of cranial kinesis. Leptoptilus javanicus possesses, in the lateral portion of the cranium, an emargination of the rostrodorsal edge of the postorbital process, not observed in either Leptoptilus dubius or Leptoptilus crumeniferus. The fossa ventralis possesses a projection in the caudal extremities in L. dubius and L. crumeniferus, which is absent in L. javanicus. The transpalatine process is present in both L. dubius and L. crumeniferus and is absent in L. javanicus. The pterygoid process of the palatine is short in both L. dubius and L. crumeniferus, and long in L. javanicus. The ectethmoid is reduced in both L. dubius and L. javanicus, whereas in L. crumeniferus, besides being more developed, it presents a “U” shape. Based on the present study, L. dubius and L. crumeniferus are phylogenetically closer to each other than L. javanicus.